2020
DOI: 10.1111/jerd.12629
|View full text |Cite
|
Sign up to set email alerts
|

Surface degradation evaluation of different self‐adhesive restorative materials after prolonged energy drinks exposure

Abstract: Aim: To evaluate the effects of energy drinks and soft beverages on the surface degradation of different self-adhesive materials. Materials and methods: A 156 disc shaped specimens of each of the following materials were prepared: Alkasite (Cention N, CN), High viscozity glass ionomer (Equia Forte, EF), Glass Carbomer (GCP Fill, GC) (n = 52). After specimen preparations, baseline surface roughness measurements were done using a 3D non-contact optical profilometer. Then, specimens were subdivided into 4 subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In contrast, the erosive potential of the green smoothie drink led to a significant Ra increase for all materials, with ΔRa values 7–26 times higher compared to the control group. This wide range of values is indicative of a highly material-dependent behavior and is above the range of results reported in the literature, namely ΔRa for glass ionomers and composites immersed in energy drinks and Coca-Cola was 2–13 times higher than in the distilled water [ 16 ], while for multivitamin syrups and effervescent tablets, 2–4 times higher ΔRa values were reported [ 15 ]. Although the results of these studies cannot be directly compared to our data due to different experimental conditions, the considerable erosive potential of a green smoothie indicated by the present study should be further investigated.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, the erosive potential of the green smoothie drink led to a significant Ra increase for all materials, with ΔRa values 7–26 times higher compared to the control group. This wide range of values is indicative of a highly material-dependent behavior and is above the range of results reported in the literature, namely ΔRa for glass ionomers and composites immersed in energy drinks and Coca-Cola was 2–13 times higher than in the distilled water [ 16 ], while for multivitamin syrups and effervescent tablets, 2–4 times higher ΔRa values were reported [ 15 ]. Although the results of these studies cannot be directly compared to our data due to different experimental conditions, the considerable erosive potential of a green smoothie indicated by the present study should be further investigated.…”
Section: Discussionmentioning
confidence: 67%
“…These conditions cause a gradual degradation of mechanical and chemical properties, consequently affecting the service life of dental restorations [ 10 ]. A number of previous studies have shown that acidic dietary foods and beverages can cause surface degradation for various types of dental restorative materials [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Concurrently with the increasing consumption of soft and fruit drinks, their potential for damaging dental hard tissues and restorative materials is becoming an important factor affecting the lifespan of contemporary dental restorations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the solution to these problems, many companies producing dental materials have worked on 'self-adhesive' systems to simplify the bonding procedures of the restorative material to the dental tissue. Self-adhesive materials bond chemically to hydroxyapatite by monomers that can etch enamel and dentin [ 5 ]. In addition, some self-adhesive materials developed have the feature of 'releasing fluoride ions' against caries, which is still a common problem today.…”
Section: Introductionmentioning
confidence: 99%
“…These self-adhesive materials can also be applied as bulk-fill. [5][6][7] Recently, a new self-adhesive bulk-fill material Cention N (Ivoclar Vivadent, Schaan, Liechtenstein) has been introduced. This material, defined as alkasite, is essentially a subgroup of composite resin.…”
Section: Introductionmentioning
confidence: 99%